Alokasi Waktu Pramuniaga pada Keluarga di Kota Makassar - Firdaus W. Suhaeb (Rayhan Intermedia, 2022)
This study aims to determine the socio-economic aspects of the driving force married women working so that entrance into the public sector as a clerk in the city of Makassar Mall Panakukang; and large allocation of time women workers who work as clerks at the Mall Panakukang family than working the household.This study used qualitative methods with descriptive approaches, techniques of collecting data through observation, interviews, documentation, and triangulation. Sampling using a purposive sampling technique on 20 people informant. The results showed that the factors driving the woman works as a saleswoman at the Mall Panakukang Makassar, the social aspects include: the future of children, husband's work, and self-actualization. While the economic aspect includes: husband's income, expenditure in the household, and the desire to save money. The division of time allocation in women workers as a salesman families were divided into 3 groups of the division of time, ie before going to work, while he was at work and after returning to work is 8 hours of working time so that 16 hours of rest that is used to take care of household chores. The impact is felt for the families of the working woman working woman is still helping their families in meeting the economic needs of working women, although her family has had its own domestic life.